Isolation and Harvesting of Lumpy skin disease virus (LSDV) strain from infected cattle breeds, Bos indicus and Bos taurus, in Sindh, Pakistan, from in-vivo Vero cell line culture to stabilize LSDV, an insight through NGS sequencing and quality analysis - Kanwal, Roohi; Kolhoro, Nazeer Hussain; Zehra, Sitwat; Kanwal, Benazir; Asif, Ehtesham; Faisal, M.; Saleem, Saima (Biological and Clinical Sciences Research Journal, 2025)
Lumpy Skin Disease Virus is an economically important poxviral pathogen of cattle that causes nodular skin lesions, reduced milk yield, and trade limitations. Molecular characterization, including whole-genome sequencing, can reveal markers of disease susceptibility and inform diagnostic and preventive strategies. Objective: To identify, isolate, and characterize Lumpy Skin Disease Virus strains circulating in native and exotic cattle in Sindh Province, Pakistan, and to assess their in vitro behaviour during cell-culture adaptation and stabilization. Methods: A field-based sampling of clinically suspected cattle cases was conducted under veterinary supervision in Sindh Province. Laboratory confirmation of infection was performed using validated molecular and serological assays. LSDV-positive samples were subjected to controlled recovery and propagation in accredited cell-culture facilities, followed by phenotypic evaluation during adaptation and stabilization phases. Whole-genome sequencing and comparative genetic analysis were performed to assess diversity among isolates relative to reference strains. All procedures were completed in accordance with approved biosafety and animal welfare protocols. Results: LSDV infection was successfully confirmed in the selected field samples using standardized molecular and serological methods. Viable viral isolates were recovered and showed consistent replication patterns during cell-culture adaptation and stabilization. Comparative phenotypic evaluation demonstrated distinguishable growth characteristics across isolates. Genomic analysis revealed measurable diversity between local strains and reference isolates, suggesting region-specific viral evolution. These findings provide actionable molecular evidence to strengthen surveillance and diagnostic preparedness in Sindh. Conclusion: The study successfully identified and characterized LSDV strains endemic to Sindh Province and demonstrated notable phenotypic and genomic variability. These insights support improved regional surveillance, diagnostic capacity, biosafety planning, and vaccine policy development. Enhanced molecular understanding will contribute to more effective control measures and reduced economic and welfare losses in affected cattle populations.